Barriers to Early Diagnosis and Treatment among Breast Cancer Survivors: Qualitative Study in Tertiary Care Hospital, North Karnataka - Nandini C; Roopakala N; Andanigoudar, Kashavva B (National Journal of Community Medicine, 2022)
Introduction: Around the World, Breast cancer has become one of the common cancers among women. Prevalence and mortality of Breast cancer in India are 18 lakh & 12.7 per lakh cases respectively. One of the important reasons behind late presentation & high death rate is the lack of breast cancer awareness. Objectives: To assess the barriers in diagnosis and treatment among breast cancer patients and to explore the perception about cancer prevention among them. Methods: A qualitative study was done among women with confirmed breast cancer who were admitted to KIMS, Hubballi, and Cancer hospital, Navanagar in April 2019. Data collection was done by the In-depth interview method and analyzed as per qualitative study protocol standards. Results: The data was collected among 14 participants. Themes were generated accordingly. The findings showed lack of awareness, myths, financial constraints, negligence were the major barriers to the early presentation of breast cancer. Conclusion: This study showed barriers such as lack of awareness, negligence, fear, financial constraints, myths and misconceptions, social stigma, lack of family support. Measures taken to reduce mortality by early diagnosis and treatment.